Intrusive memories in perpetrators of violent crime: emotions and cognitions. - Evans, C; Ehlers, A; Mezey, G; Clark, D (2007)
The authors investigated factors that may determine whether perpetrators of violent crime develop intrusive memories of their offense. Of 105 young offenders who were convicted of killing or seriously harming others, 46% reported distressing intrusive memories, and 6% had posttraumatic stress disorder. Intrusions were associated with lower antisocial beliefs before the assault, greater helplessness, fear, dissociation, data-driven processing and lack of self-referent processing during the assault, more disorganized assault narratives, and greater negative view of the self, negative interpretations of intrusive memories, perceived permanent change, and self-blame. In a logistic regression analysis, the cognitive and emotional variables explained substantial variance over and above demographic factors. The results suggest that cognitive factors that predict reexperiencing symptoms in victims of crime generalize to perpetrators.